THE NUMBER “BIR” (“ONE”) AND ITS MEANINGS IN NUMERAL-COMPONENT COMPOUND WORDS - Polvanova Nafisa Muxitdinovna (International Journal of Literature and Language Studies, 2026)
It is well known that, in compound words containing numeral components, words belonging to the numeral category and functioning as the first component play an important role. Therefore, we became interested in determining which numerals occur most frequently in such compounds and found that the numeral “bir” (“one”), the first and basic numeral, participates as a component in a large number of words. Consequently, we will attempt to analyze the numeral “bir” in greater depth.